Pengaruh Stress Kerja Dan Motivasi Terhadap Kinerja Pengusaha Usaha Mikro Kecil Menengah - Wima Fiarry Virliyanna (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of work stress and motivation on the performance of micro, small and medium enterprises entrepreneurs. This type of research is quantitative. The variables in this study are work stress variables (X1), motivation (X2) and performance (Y). The sample in this study amounted to 34 respondents. The data used is primary data. The data collection instrument in this study was to distribute questionnaires. The analysis technique used is multiple linear regression. Based on hypothesis testing using the f test simultaneously that the value of work stress and motivation variables is smaller than a (0.000 <0.05) and f count 17.175> f table value 3.30, it can be concluded that there is an influence of work stress and motivation on the performance of micro, small and medium entrepreneurs.